Secondary malposition of a PICC-port due to heavy physical exercise: A case report. Issue 3 (May 2023) - D'Arrigo, Sonia; Annetta, Maria Giuseppina; Musarò, Andrea; Distefano, Mariagrazia; Pittiruti, Mauro
Physical exercise is often encouraged in cancer patients, mainly for the purpose of rehabilitation and for its psychological benefit. Some authors also suggest that exercise—specially in patient with peripherally inserted central venous access devices—may contribute to reduce the risk of catheter-related thrombosis. Still, the impact of physical exercise on the risk of device-related complications is not yet defined. We report a case of secondary migration of the tip of an arm port, caused by high-intensity exercise in a woman undergoing chemotherapy because of ovarian cancer. Tip migration was suspected because of malfunction (persistent withdrawal occlusion) and diagnosis established after ultrasound examination and chest x-ray. Even if exercise may yield benefit in the cancer patient on chemotherapy, the risk of mechanical complication of the venous access device—such as tip migration—should be considered in the case of high-intensity exercise.